Estimasi Biaya Penggunaan Semen Instan (Mortar) Vs Semen Konvensional Pada Pekerjaan Dinding Rumah Sederhana (Studi Kasus : Luwu Timur) - Nur Ainun; Anggel Erpa Erong Pakiding (CV. SINAR HOWUHOWU, 2026)
Wall work is one of the components with the largest volume in the construction of a simple house which greatly affects the cost efficiency of the project. This study aims to compare the estimated cost of using instant cement (Mortar) with conventional cement (a mixture of Portland cement and sand) in the masonry and plastering work of the walls of a simple type 36 house in East Luwu Regency. A comparative descriptive quantitative approach based on the Work Unit Price Analysis (AHSP) of the Minister of PUPR Regulation, namely by transferring the real volume of the building to the basic price of materials available in East Luwu. The results of the analysis show that although the retail purchase price of instant cement (Mortar) per sack is more expensive, material consumption per square meter is much less and is able to reduce the labor wage coefficient due to the faster work duration. Accumulatively in a type 36 house with a wall volume of 92 m2, the use of instant cement (mortar) results in a total cost of Rp 10,115,400, while conventional cement is Rp 13,248,000. Thus, the use of instant cement provides a cost efficiency of 23.65% and minimizes material waste in the field.